A stable electrode for high-potential, electrocatalytic O(2) reduction based on rational attachment of a blue copper oxidase to a graphite surface. - Blanford, C; Heath, R; Armstrong, F (2007)
Attachment of substrate-like anthracene based units to the surface of pyrolytic graphite greatly enhances the adsorption of high-potential fungal laccases, 'blue' Cu enzymes that catalyse the four-electron reduction of O(2), providing a stable cathode for enzymatic biological fuel cells and electrochemical studies.